Clinical Outcome of Sacral Chordoma Patients Treated with Pencil Beam Scanning Proton Therapy. Issue 12 (December 2021) - Walser, M.; Bojaxhiu, B.; Kawashiro, S.; Tran, S.; Beer, J.; Leiser, D.; Pica, A.; Bachtiary, B.; Weber, D.C.
Abstract: Aims: Sacral chordomas are locally aggressive, radio-resistant tumours. Proton therapy has the potential to deliver high radiation doses, which may improve the therapeutic ratio when compared with conventional radiotherapy. We assessed tumour control and radiation-induced toxicity in a cohort of sacral chordoma patients treated with definitive or postoperative pencil beam scanning proton therapy. Methods and materials: Sixty patients with histologically proven sacral chordoma treated between November 1997 and October 2018 at the Paul Scherrer Institute with postoperative ( n = 50) or definitive proton therapy ( n = 10) were retrospectively analysed. Only 10 (17%) patients received combined photon radiotherapy and proton therapy. Survival rates were calculated using the Kaplan–Meier actuarial method. The Log-rank test was used to compare different functions for local control, freedom from distant recurrence and overall survival. Acute and late toxicity were assessed according to the Common Terminology Criteria for Adverse Events (CTCAE) v5.0. Results: The median follow-up was 48 months (range 4–186). Local recurrence occurred in 20 (33%) patients. The 4-year local control, freedom from distant recurrence and overall survival rates were 77%, 89% and 85%, respectively. On univariate analysis, subtotal resection/biopsy ( P = 0.02), tumour extension restricted to bone ( P = 0.01) and gross tumour volume >130 ml ( P = 0.04) were significant predictors for local recurrence. On multivariate analysis, tumour extension restricted to bone ( P = 0.004) and gross total resection ( P = 0.02) remained independent favourable prognostic factors for local recurrence. Twenty-four (40%), 28 (47%) and eight (11%) patients experienced acute grade 1, 2 and 3 toxicities, respectively. The 4-year late toxicity-free survival was 91%. Two patients developed secondary malignancies to the bladder 3–7 years after proton therapy. Conclusions: Our data indicate that pencil beam scanning proton therapy for sacral chordomas is both safe and effective. Gross total resection, tumour volume <130 ml and tumour restricted to the bone are favourable prognostic factors for local tumour control. Highlights: Proton therapy in sacral chordoma patients is effective and save. Tumour extension is an important prognostic factor. Gross tumour resection provides highest chance for local control.